The Ethnographic Case - Yates-Doerr, Emily; Labuski, Christine (Mattering Press, 2024)
The 1st Edition of The Ethnographic Case, published in 2017, was an experiment in post-publication peer review, with the book published online and open to comments from readers. In this new 2nd edition, to be published later this year, the editors and authors have updated the text, both in response to these comments and taking into account changing contexts in the years since the book’s first publication.